The role of pigment epithelium-derived factor in protecting against cellular stress. (2nd December 2019) - Brook, Naomi; Brook, Emily; Dharmarajan, Arun; Chan, Arlene; Dass, Crispin R.
Abstract: Since its discovery as a neurotrophic factor in retinal pigmented epithelium cells in the late 1980s, there has been an increase in understanding of the role that pigment epithelium-derived factor (PEDF) plays in cellular functions. PEDF plays an important role in mediating cellular protection during exposure to oxidative stress and inflammation by preventing stress-induced angiogenesis and apoptosis. PEDF acts to reduce oxidative stress by promoting mitochondrial stability and by regulating the expression of enzymes involved in ROS accumulation and clearance. PEDF protects against the negative effects of oxidative stress by regulating cell survival pathways and the expression of inflammatory and proangiogenic mediators. PEDF-mediated cellular protection may be of clinical importance in diseases characterised by oxidative stress, chronic inflammation and pathological neovascularization, indicating that targeting PEDF may be a potential focus for therapeutic interventions in chronic diseases. In this review, we provide a historical perspective on the discoveries of PEDF interactions and functions, and discuss recent in vitro, in vivo and clinical findings to provide a current summary of the important protective effects following cellular exposure to stress stimuli and future clinical potential of PEDF.